2023
DOI: 10.3233/jhd-220557
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Role of Tau in Huntington’s Disease Pathology

Abstract: There is increasing evidence for the presence of pathological forms of tau in tissues of both Huntington’s disease (HD) patients and animal models of this condition. While cumulative studies of the past decade have led to the proposition that this disorder could also be considered a tauopathy, the implications of tau in cellular toxicity and consequent behavioral impairments are largely unknown. In fact, recent animal work has challenged the contributory role of tau in HD pathogenesis/pathophysiology. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Also, diffusion imaging has demonstrated that the corpus callosum (the largest white matter structure in the brain) is thinner in HD gene carriers, and this thinning has been linked to the degeneration of callosal axons and myelination deficits (Casella et al, 2020). Significant increases in Tau plasma levels have been observed in the advanced stages of different mouse models of HD (Salem & Cicchetti, 2023). On the other hand, a significant increase in Tau has been detected in neural stem cells derived from the developing forebrain of YAC128 mice (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, diffusion imaging has demonstrated that the corpus callosum (the largest white matter structure in the brain) is thinner in HD gene carriers, and this thinning has been linked to the degeneration of callosal axons and myelination deficits (Casella et al, 2020). Significant increases in Tau plasma levels have been observed in the advanced stages of different mouse models of HD (Salem & Cicchetti, 2023). On the other hand, a significant increase in Tau has been detected in neural stem cells derived from the developing forebrain of YAC128 mice (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…the advanced stages of different mouse models of HD (Salem & Cicchetti, 2023). On the other hand, a significant increase in Tau has been detected in neural stem cells derived from the developing forebrain of YAC128 mice (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since HD patients show brain-wide aggregated TAU inclusions, HD is classified as a secondary tauopathy [ 216 ]. The haplotype of MAPT influences the clinical picture in HD, patients with the H2 MAPT haplotype present a more rapid cognitive decline compared to the H1 carriers, indicating a disease driving role for TAU in HD [ 217 , 218 ]. Hence, therapeutic approaches for the treatment of HD besides targeting HTT comprise targeting of TAU similar to AD, including modulation of MAPT gene expression, inhibition of TAU aggregation, targeting hyperphosphorylated TAU, and TAU immunotherapies [ 219 ].…”
Section: Secondary Tauopathiesmentioning
confidence: 99%
“…Although TAU may be a driver of pathogenic changes in HD as it is hyperphosphorylated already in early disease stages, modulation of TAU expression in HD mice does not influence the progression of the HD phenotypes [ 224 , 225 ]. For review on the implications of TAU dysregulation in HD see Mees et al [ 222 ] and Salem and Cicchetti [ 217 ]. In sum, while there is evidence for a role of TAU as a contributor or even disease driver, it may not be an ideal therapeutic target for HD.…”
Section: Secondary Tauopathiesmentioning
confidence: 99%
“…This expansion triggers the toxic form of the Huntingtin protein, leading to synaptic impairment, mitochondrial dysfunction, and disrupted axonal transport, ultimately contributing to motor, cognitive, and psychiatric impairments ( Baake et al, 2017 ; Ghosh and Tabrizi, 2018 ). Emerging research also suggests that HD may be classified as a secondary tauopathy, with tau insoluble aggregates observed in late-stage HD ( Salem and Cicchetti, 2023 ). Furthermore, there is increased activity of pGSK-3β-Tyr216 in the hippocampus of HD patients and mice, underscoring the potential significance of abnormal GSK-3β signaling in HD progression ( L'Episcopo et al, 2016 ).…”
Section: Gsk-3β In Hdmentioning
confidence: 99%